Assessing the Impact of Entrepreneurship Education on Fostering Entrepreneurial Intention among Entrepreneurship Students - Bernardo, Joana Marie (JPAIR Multidisciplinary Research, 2026)
This study examines the impact of entrepreneurship education on fostering entrepreneurial intention among students specializing in entrepreneurship. Using a quantitative research design, data were collected through survey questionnaires to analyze the relationship between entrepreneurship education and key factors influencing entrepreneurial intention, including attitudes toward entrepreneurship, subjective norms, and perceived behavioral control. The findings reveal statistically significant relationships among these variables, with most respondents strongly agreeing that these factors influence their decision to pursue entrepreneurial careers. A general weighted average of 4.35 indicates a high level of readiness and commitment among participants to engage in entrepreneurial activities. These results support previous research suggesting that entrepreneurship education positively shapes students’ entrepreneurial mindsets and intentions. The findings highlight the importance of creating supportive academic and social environments that strengthen students’ confidence and entrepreneurial readiness. The study provides practical insights for educators and policymakers in designing effective entrepreneurship programs that encourage students to pursue entrepreneurial ventures.